2013
DOI: 10.3109/02699052.2013.823662
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Depression Anxiety Stress Scales in individuals with traumatic brain injury

Abstract: These results indicate that it may be preferable to use the full DASS, rather than the DASS21, with individuals with TBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Indeed, some studies found that such combination therapy reduced mortality, infarct size, and improved left ventricular function, accompanied by increased homing of bone marrow cells to the infarcted myocardium and formation of new cardiomyocytes and ventricular structures (21). In chronic stroke studies, G-CSF + SCF induced more stable and long-lasting functional improvement compared with treatment with SCF or G-CSF alone, attributable to increased angiogenesis and neurogenesis through bone marrow-derived cells and the direct effects on stimulating neurons to form new neuronal networks (126).…”
Section: Therapeutic Uses Of G-csfmentioning
confidence: 99%
“…Indeed, some studies found that such combination therapy reduced mortality, infarct size, and improved left ventricular function, accompanied by increased homing of bone marrow cells to the infarcted myocardium and formation of new cardiomyocytes and ventricular structures (21). In chronic stroke studies, G-CSF + SCF induced more stable and long-lasting functional improvement compared with treatment with SCF or G-CSF alone, attributable to increased angiogenesis and neurogenesis through bone marrow-derived cells and the direct effects on stimulating neurons to form new neuronal networks (126).…”
Section: Therapeutic Uses Of G-csfmentioning
confidence: 99%
“…In moderate to severe trauma, TBI survivors present with chronic disabilities associated with loss of primary cerebral parenchymal tissues, secondary cell death including apoptosis, and exacerbated neuroinflammation [9], [10], [11]. Among the worst outcomes, sensorimotor dysfunctions, massive hippocampal cell death, learning and memory impairments, aphasia, anxiety, and dementia are the most prevalent [12], [13], [14], [15], [16]. At present, clinical treatments are limited and the few that have been utilized have proven to be ineffective in most of the TBI cases [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…This scale was first introduced in 1995 by Lovibond (27) and ever since is used in various foreign studies (28)(29)(30). The reliability and validity of this scale is confirmed for patients with MS in Iran (r = 0.89) (31).…”
Section: Questionnairementioning
confidence: 99%